GAMBARAN GINGIVITIS PADA PEROKOK REMAJA DI DESA KUANG DALAM TIMUR, KEC. RAMBANG KUANG KABUPATEN OGAN ILIR TAHUN 2021 - Tri Syahniati; Wanda Chairunnisa; Sulaiman Sulaiman; Dhandi Wijaya (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Palembang, 2021)
Background: Smoking is one of the bad habits that are often encountered in everyday life. Smoking habits can cause various diseases in the body, one of which is gingivitis or gingivitis. Gingivitis is usually characterized by changes in the color and texture of the gingiva/gums in accordance with the continuous increase in the inflammatory process. Objective: To find out the description of gingivitis in adolescent smokers in Kuang Dalam Timur Village, Rambang Kuang District, Ogan Ilir Regency in 2021. Methods: This is a descriptive study. The sample size in this study were 60 people who were taken using total sampling technique. Results: In all respondents with a duration of smoking <5 years to >10 years, most of them experienced moderate gingivitis, and in all types of smokers, most of them also experienced moderate gingivitis but in heavy smokers there was no normal (healthy) gingiva. Most of the filter smokers suffer from moderate gingivitis (47%) and the non-filter smokers mostly have severe gingivitis (57%) and there is no normal gingiva. Mild gingivitis mostly affects the lower jaw (44%), moderate gingivitis mostly affects the upper jaw (37%), and severe gingivitis affects both the lower and upper jaws. Conclusion: The duration of smoking and the number of cigarettes smoked tend to aggravate gingivitis. Non-filter cigarettes are more likely to cause gingivitis than filter cigarettes. The degree of gingivitis affects the extent of the gingival area affected.